ADJECTIVE PHRASE CONSTRUCTION INDICATED IN STUDENTS DESCRIPTIVE TEXT: A CROSS SECTIONAL STUDY ON STUDENTS OF SMA NEGERI 1 MATAULI PANDAN TAPANULI TENGAH - Erma Hermawar; Rahmat Husein; Audi Yundayani (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2021)
This study investigates the types of interlanguage of adjective phrase construction that students made when writing English descriptive text. The errors function as a system and can be used to determine interlanguage. The researcher employed a cross-sectional design and used descriptive qualitative methods. The descriptive texts of the students were collected as primary data at the same time but different levels of proficiency. Thirty tenth-grade students from Matauli Senior High School in Central Tapanuli, North Sumatera, participated in the study. Error Analysis (EA) and Interlanguage theories were central to the data analysis (IL). The findings revealed that students' English production is still interlanguage because their writings contain a wide range of errors regarding adjective phrases. There are 113 errors in total. There are up to 70 items of omission errors (62%), 19 items of misformation errors (17%), 15 items of misordering errors (13%), and 9 items of addition errors (8%). Furthermore, four processes were identified as contributing to students' interlanguage in this study, with the student's native language having the greatest influence on their English production (Language transfer (71%), second language learning strategies (14%), false concepts hypothesized (9.7%), and overgeneralization (5.3%)). The findings also revealed that both interlingual and intralingual sources have caused errors in second language learning. It can be concluded that students' competence at each level is insufficient. Due to their system, they are on the interlanguage continuum, which has a structurally intermediate status between the native and target languages.